2011
DOI: 10.1375/brim.12.2.128
|View full text |Cite
|
Sign up to set email alerts
|

Compassion Focused Therapy After Traumatic Brain Injury: Theoretical Foundations and a Case Illustration

Abstract: Acquired brain injury (ABI) commonly results in a range of interacting difficulties including regulating emotion, managing social interactions and cognitive changes. Emotional adjustment to ABI can be difficult and requires adaptation of standard psychological therapies. This article outlines a case where cognitive– behavioural therapy (CBT) was of limited effectiveness but was significantly enhanced with compassion focused therapy (CFT). This article describes Jenny, a 23-year-old woman who suffered a traumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 53 publications
2
61
0
1
Order By: Relevance
“…For activity-based interventions specifically, there was evidence from two RCTs (Blake & Batson, 2009;Driver et al, 2006), one pre-post group study (Fines & Nichols, 1994) and a case series (Schwandt et al, 2012) that exercise and active leisure were helpful in improving selfconcept after TBI. There was also some evidence of improvement in selfconcept in an RCT of family-based support (Sinnakaruppan et al, 2005), and a case study of psychotherapy (Ashworth et al, 2011). While another five RCTs found positive effects in the functional domain targeted by the intervention (Anson & Ponsford, 2006;Gemmell & Leathem, 2006;Hodgson et al, 2005;Medd & Tate, 2000;Simpson et al, 2011), this did not generalise to global self-concept.…”
Section: Discussionmentioning
confidence: 99%
“…For activity-based interventions specifically, there was evidence from two RCTs (Blake & Batson, 2009;Driver et al, 2006), one pre-post group study (Fines & Nichols, 1994) and a case series (Schwandt et al, 2012) that exercise and active leisure were helpful in improving selfconcept after TBI. There was also some evidence of improvement in selfconcept in an RCT of family-based support (Sinnakaruppan et al, 2005), and a case study of psychotherapy (Ashworth et al, 2011). While another five RCTs found positive effects in the functional domain targeted by the intervention (Anson & Ponsford, 2006;Gemmell & Leathem, 2006;Hodgson et al, 2005;Medd & Tate, 2000;Simpson et al, 2011), this did not generalise to global self-concept.…”
Section: Discussionmentioning
confidence: 99%
“…Having a greater understanding of self-conscious emotions such as shame following brain injury and their role in the emotional adjustment process would be clinically useful in informing neuropsychological rehabilitation approaches (Ashworth, Gracey, & Gilbert, 2011). Specific approaches aimed at addressing shame and the response of self-criticism include compassion-focused therapy (Gilbert & Procter, 2006), although this has yet to be empirically tested in a TBI population.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%
“…For those individuals experiencing shame or guilt, using therapeutic approaches such as narrative therapy (Cloute, Mitchell, & Yates, 2008;Morgan, 2000) or a compassion-focused therapy approach (Gilbert, 2007;Ashworth et al, 2011), which are based on theoretical frameworks addressing issues of shame, social-construction and stigma, may be helpful.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%
“…CFT has been shown to be helpful for people with psychosis [18,19] and can significantly reduce paranoid ideation [20] and emotional difficulties for people with personality disorder difficulties [20]. Ashworth et al [21] found CFT to be a valuable addition to standard interventions in helping people with acquired brain injury. Kuyken et al [22] found that in a mindfulness trial, self-compassion was a significant mediator between mindfulness change and recovery from depression.…”
Section: Introductionmentioning
confidence: 99%